Między oczekiwaniami a rzeczywistością – perspektywa zawodowa kandydatów do zawodu i początkujących nauczycieli wczesnej edukacji - Justyna Kosz-Szumska (Problemy Wczesnej Edukacji)
The paper addresses theoretical considerations focusing on the career choice motives of early childhood education teachers in the light of a review of previous research, and it presents the research problem along with an analysis of results. The aim of this study was to determine the motives for choosing the profession of early childhood education teacher by students of early childhood pedagogy, graduating with a bachelor’s degree, and early childhood education teachers working in the profession for no more than five years. A diagnostic survey method was used, with a questionnaire technique. The results indicate that the choice of early childhood education teachers is a product of internal and external motives, with the former having a dominant role. Meeting psychological needs (including the desire to work with children, personality predispositions) is combined with pragmatic qualities – e.g. days off, low weekly working hours. Both groups surveyed recognize the problem of low professional prestige and the financial unprofitability of the teaching profession. The motivations for studying early childhood pedagogy are personal predispositions, interests and directional talents. The sense of rightness regarding the choice of a professional path increases with the acquisition of practice, which corresponds to the sense of preparation for the profession. The current system of pedagogical internships does not provide sufficient practical preparation for a job as an early childhood education teacher.